A quantitative analysis of the size of IMF resources - Pilar LHotellerie-Fallois; Menno Broos; Sonsoles Gallego Herrero; Isabel Garrido Chamorro; Fernando López Vicente; Mayukh Mukhopadhyay; Claudia Maurini; Benjamin Vonessen (European Central Bank (ECB), 2018)
In this report, three methodological approaches are applied to assess the size of the International Monetary Fund: benchmarking Fund resources against a number of relevant global economic and financial indicators; an extrapolation of past and current IMF programme characteristics; and a shock scenario analysis. Overall, while the results of the different approaches depend on the assumptions and the timeframe considered, the quantitative analysis indicates that a prudent approach would call for maintaining Fund total resources at their current levels. Yet, the quantitative analysis of the size of the Fund made in this report should be seen only as one element to assess the adequacy of Fund resources. It does not take into account qualitative considerations, such as the increased resilience of the global economy and the efforts made to strengthen regulation and supervision since the financial crisis, which should complement the quantitative analysis to complete the analytical basis for decision makers. Moreover, the final decision on the appropriate size of Fund resources will need to include political judgement. Therefore, this report does not provide recommendations on the appropriate level of IMF resources after the expiration of borrowed resources.
Keywords: F3; F32; F38; F42; F65; G28; 330; IMF; GFSN; shock scenario analysis